2018
DOI: 10.1108/ijcma-09-2017-0100
|View full text |Cite
|
Sign up to set email alerts
|

Resentment against the rich

Abstract: Purpose Because of increasing wealth inequality, China has been confronted with resentment against the rich (referred to hereafter as RAR or Choufu in Chinese), which is a growing concern owing to its potential to foment social conflict. Drawing on social comparison and deonance theories, this paper aims to provide theoretical insights into RAR within the Chinese context and to develop an RAR scale. Following spillover theory, the attitudinal and behavioral outcomes of RAR in organizational settings will be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 109 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…A small but growing number of studies have found links between economic or social inequality on the one hand and employee attitudes and behaviors on the other. For instance, various employee outcomes such as ethical thinking (Chen, 2014 ), absenteeism (Andrews & Htun, 2018 ), bullying (Soylu & Sheehy-Skeffington, 2015 ), satisfaction (Wu & Lin, 2018 ) and health outcomes (Jiang & Probst, 2017 ) have been linked to socio-economic inequality (see Bapuji et al, 2020a , for a review).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…A small but growing number of studies have found links between economic or social inequality on the one hand and employee attitudes and behaviors on the other. For instance, various employee outcomes such as ethical thinking (Chen, 2014 ), absenteeism (Andrews & Htun, 2018 ), bullying (Soylu & Sheehy-Skeffington, 2015 ), satisfaction (Wu & Lin, 2018 ) and health outcomes (Jiang & Probst, 2017 ) have been linked to socio-economic inequality (see Bapuji et al, 2020a , for a review).…”
Section: Hypothesis Developmentmentioning
confidence: 99%